Dampak covid-19 pada pasar saham di berbagai negara - Fauziyyah, Nurul; Ersyafdi, Ilham Ramadhan (Faculty of Economics and Business Mulawarman University, 2021)
COVID-19 is an unbelievable infectious disease that first emerged in China and then spread widely to other countries around the world. This pandemic which initially caused extraordinary turmoil in the health sector has gradually devastated other sectors such as education, eeconomic, financial, especially the world stock market. The unbalance condition of the world stock market began since the announcement of COVID-19 by WHO and until now the COVID-19 pandemic has not been completely resolved so that this uncertainty makes the world stock market experiencing negative turmoil. This paper aims to provide an overview of global stock market conditions at the time of the COVID-19 pandemic. This study was conducted by previous studies and associated with current information, data from credible sources, and several book references or also known as literature study. Stock market data are taken from the official stock exchange websites of each country using closing share prices at the end of each month from January to March 2020. The data analysis method used in this study is descriptive analysis method. Results showed that various countries in the world experienced a negative turmoil on their stock markets due to the presence of COVID-19 and the worst condition occurred on March 2020. In addition, among other pandemics that have occurred before, COVID-19 is one of the most shocking pandemics in the world, especially on the stock market. However, stock markets in ASIA were more severely affected than in Europe.